The Fermentation Effects of Lactobacillus casei to Sweet Corn Physical Characteristic - Ntau, Liean; Sumual, Maria F.; Assa, Jan R. (Pascasarjana Unsrat, 2017)
The purpose of this research is to reveal the physical properties of fermented corn meal using Lactobacillus casei bacteria. Completely Randomized Design (CRD) was used in this research. Lactobacillus casei was use for the fermentation of sweet corn grits and the treatments were duration (hour) of fermentation i.e. without fermentation (control), 24, 48 dan 72 hours. The observed variables were physical properties of sweet corn flour. The results showed that sweet corn flour produced after fermentation has an average of gelatinization temperature ranged between 59 0C – 64,67 0C and have a level of brightness L * 81.33 – 82.60, the colors a * -0.27 – 3.03 and b * 27.60 – 30.50. The water absorption capacity ranged betwen 40.53% – 65.33%, oil absorption 31% – 47% and the average yield of sweet corn flour after fermentation ranged between 12.63% – 29.24%. The Swelling power of corn flour was maximum at 95 0C and it ranged between 8.23 g/g – 6.57 g/g. Fermentation of sweet corn grits by Lactobacillus casei for 72 hours significanthy affected yield and swelling power of sweet corn flour.Keywords: Lactobacillus casei fermentation, physical properties of flour, sweet corn